Effect of Fibre (Polypropylene) Volume in Mortar Mixed With POFA - Raudhah, Ahmadi; Dora Ediba, Lucas; Mohd Syukry, Saiful; Mohammad, Abdul Mannan (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
High strength fibre reinforced concrete is envisaged to exhibit high compressive and tensile strength under loadings. In this study, experimental studies are conducted to assess the mechanical behavior of fibre reinforced mortar and comparing them with normal concrete. For this experiment, the aspect ratio of fibre (polypropylene) volume inclusion is fixed to 33. Palm Oil Fuel Ash (POFA) is also included as partial cement replacement. The compressive strength and split tensile strength tests are conducted. This paper presents the results of mechanical strength for fibre reinforced mortar mixed with POFA. It is indicated that the volume of fibre inclusion in concrete have significant impact in compressive and tensile strength. In this study, the optimum fibre dosage inclusion is 20 kg/m3 that exhibit 82.4MPa and 78.7 MPa stresses at 56 days of curing for both 100% OPC and 40%POFA inclusion samples, respectively. The findings of this study can be applied to construction in coastal areas.